Genome-Wide Analysis of the RAV Family in Soybean and Functional Identification of GmRAV-03 Involvement in Salt and Drought Stresses and Exogenous ABA Treatment - Zhao, Shu-Ping; Xu, Zhao-Shi; Zheng, Wei-Jun; Zhao, Wan; Wang, Yan-Xia; Yu, Tai-Fei; Chen, Ming; Zhou, Yong-Bin; Min, Dong-Hong; Ma, You-Zhi; Chai, Shou-Cheng; Zhang, Xiao-Hong (Frontiers in Plant Science, 2017)
Transcription factors play vital roles in plant growth and in plant responses to abiotic stresses. The RAV transcription factors contain a B3 DNA binding domain and/or an APETALA2 (AP2) DNA binding domain. Although genome-wide analyses of RAV family genes have been performed in several species, little is known about the family in soybean (Glycine max L). In this study, a total of 13 RAV genes, named as GmRAVs, were identified in the soybean genome. We predicted and analyzed the amino acid compositions, phylogenetic relationships, and folding states of conserved domain se-quences of soybean RAV transcription factors. These soybean RAV transcription factors were phylogenetically clustered into three classes based on their amino acid sequences. Subcellular localization analysis revealed that the soybean RAV proteins were located in the nucleus. The expression patterns of 13 RAV genes were analyzed by quantitative re-al-time PCR (qRT-PCR). Under drought stresses, the RAV genes expressed diversely, up- or down-regulated. Following NaCl treatments, all RAV genes were down-regulated excepting GmRAV-03 which was up-regulated. Under ABA treatment, the expression of all of the soybean RAV genes increased dramatically. These results suggested that the soybean RAV genes may be involved in diverse signaling pathways and may be responsive to abiotic stresses and exogenous ABA. Further analysis indicated that GmRAV-03 could increase the transgenic lines resistance to high salt and drought and result in the transgenic plants insensitive to exogenous ABA. This present study provides valuable information for understanding the classification and putative functions of the RAV transcription factors in soybean.